Gastroprotective effects of aquous solution: Acacia catechu on gastric mucosal injury in experimental albino rats model - Waseem, Uzma; Waseem, Anoosha; Majeed, Nadia; Qureshi, Fauzia; Muneer, Muhammad Qasim; Jafri, Syeda Rizwana (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Around the globe, acid peptic disease and its potential complications are among the major cause of morbidity and is a significant burden on health system. Till now, the main stay of treatment are the pharmaceutical agents which decrease the secretion of acid. But these have potential complications and tolerability issues. Among such plants one is Acacia catechu commonly available in India and Pakistan. Methods: This experimental study involved 48 albino rats that were divided into four groups. Group A, B, C, and D were given water, 100mg aspirin, 100 mg aspirin+ 250 mg Acacia catechu and 100 mg aspirin+500 mg Aacacia catechu respectively, and were sacrificed on day 3, 7 and 14th day of study and observed for changes. Results: Difference between blood vessels in subgroup B1 and subgroup C1 with subgroup D1 was statistically significant (p=0.05) and (p=0.001). Group C1 and D1 had normal vessels in mucosa and submucosa. However, dilatation of blood vessels was noted in both groups receiving Acacia catechu along with ASA. Conclusions: Aqueous extracts of Acacia catechu stem and bark showed significant anti-ulcer and anti-inflammatory activities by increasing blood flow to the stomach.